Enhanced Production of Phytase, A Feed Enzyme, from Pichia kudriavzevii using Mutagenesis and Improved Culture Conditions - Wanatchaporn Boontham (Science Faculty of Chiang Mai University, 2019)
Pichia kudriavzevii WB17-1, a phytase-producing yeast isolated from duck excrement, was found to produce both cell-bound and extracellular phytases. To enhance extracellular phytase, P. kudriavzevii WB17-1 was subjected to induced mutation. Ethylmethane sulfonate (EMS)-induced mutation resulted in 2,400 mutants. The mutant P. kudriavzevii WB17-1 EMS3 showed the highest extracellular phytase activity. This mutant possessed a 6.2-fold increase in enzyme activity compared to the wild type level. The wild type and mutant were subjected to characterization of PHYPk, a gene encoding P. kudriavzevii phytase. An open reading frame of 1,071 bp encoding 357 amino acids with a predicted protein molecular mass of 40.056 kDa was identified. To optimize the extracellular phytase activity of P. kudriavzevii WB17-1 EMS3, a response surface methodology (RSM) was employed. The highest extracellular phytase activity was obtained in the medium containing 2.95% dextrose and 0.58% peptone with an initial pH of 5.8. The optimized phytase activity was 2.3 times the level obtained under un-optimized conditions and was 14.4 times the wild type level. The results obtained here show successful yeast strain improvement and optimization of extracellular phytase by yeast using RSM.